ANALISIS POTENSI PENERIMAAN PAJAK RESTORAN - Wahyudianti, Muthia Alvi Aulia (Journal of Development Economic and Social Studies, 2023)
Every regency/city in East Java province must provide financial resources without relying on central or provincial government funds to finance expenditures. This is supported by the existence of Regional Original Income which is a source of finance for each region. Native Revenue The area has components such as restaurant taxes that can increase that revenue. The purpose of this study is to determine the potential and factors that affect restaurant tax revenue in Malang City. The methods used in this study are potential calculations and multiple regression analysis with classical assumption tests and hypothesis tests. The data used are the number of tourists, the GRDP of the tourism sector, the number of residents, taxpayer compliance, and the number of restaurants. The data was obtained from BPS Kota Malang and the Badan Pendapatan Daerah Kota Malang. The results of this study show that the potential of Malang City every year increases and the number of tourists, GRDP of the tourism sector, population, taxpayer compliance, and the number of restaurants have a positive and significant effect on restaurant tax revenue.